2016
DOI: 10.1080/00036846.2016.1148257
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship among efficiency, capitalization and risk: does management matter in local banking market?

Abstract: By employing a Granger causality methodology in a panel data framework, this article explores the relationship among efficiency, capitalization and credit risk within the local Italian banking system. Focusing the attention on cooperative banks, we specifically test whether managers take more risks in highly concentrated markets (i.e. monopoly) than in partially competitive markets (i.e. duopoly). The evidence shows that in more concentrated markets, management efficiency generates a decrease in risk-taking (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Increasing of interest rate will increase bank's cost and decrease efficiency (Sun & Chang, 2011). Moreover, some past studies found that credit risk has negative rekationship with efficiency (Chen et al, 2015;Nguyen & Nghiem, 2015;Barra et al, 2016;Mosko & Bozdo, 2016). Meanwhile, positive relationship between credit risk and efficiency also had been revealed by and Saeed and Izzeldin (2016).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Increasing of interest rate will increase bank's cost and decrease efficiency (Sun & Chang, 2011). Moreover, some past studies found that credit risk has negative rekationship with efficiency (Chen et al, 2015;Nguyen & Nghiem, 2015;Barra et al, 2016;Mosko & Bozdo, 2016). Meanwhile, positive relationship between credit risk and efficiency also had been revealed by and Saeed and Izzeldin (2016).…”
Section: Literature Reviewmentioning
confidence: 96%
“…We follow Destefanis et al (2014), Barra, Bimonte, and Zotti (2016) and Barra and Zotti (2019) for the identification of the market structure in which banks operate. Specifically, the following market structures have been identified: (1) monopolistic (MON): municipalities where there is only one bank head‐office; (2) duopolistic (DUO): municipalities where there are two head‐offices; (3) oligopolistic case (OLIG): municipalities where there are three head‐offices; (4) competitive (COMP): municipalities in which there are more than three head‐offices.…”
Section: Empirical Designmentioning
confidence: 99%
“…Relatively instead to the computation of bank efficiency, departing from the asset model of Sealey Jr. and Lindley (1977), the choice of input and output vectors relies on a large economic literature which has been devoted to assess the efficiency of banking institutions (Mamatzakis et al, 2021; Mostak Ahamed et al, 2021; Prior et al, 2019; Tsionas & Andrikopoulos, 2020; Tsionas & Philippas, 2021) and on a stream of recent contributions which have dealt with the analysis of the efficiency of the Italian banking system (Amendola et al, 2021; Barra et al, 2016,b; Barra & Ruggiero, 2021b; Barra & Zotti, 2019; Coccorese & Ferri, 2020). Following this approach, 7 the output vector (y) comprises customer loans (y 1 ); services (administrative) or non‐traditional activities, that is, commission income and other operating income (y 2 ); and securities (y 3 ), that is, bank loans, Treasury bills, bonds and other debt less bonds and debt securities held by banks and other financial institutions.…”
Section: Empirical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the idea that banks with less local competition are able to increase their profits by indulging more freely in rent-seeking behaviour, minimizing their risk-taking. Therefore, the quality of their assets improves through additional screening processes (Barra et al 2016a).…”
Section: Financial Soundness-growth Nexus: Theoretical and Empirical Backgroundmentioning
confidence: 99%